THE INFLUENCE OF FINANCIAL LITERACY INTEGRATION AND ORGANIZATIONAL DIVERSITY ON MSME DEVELOPMENT THROUGH INNOVATION CAPABILITY AS AN INTERVENING AND EXTERNAL ENVIRONMENTAL SUPPORT AS A MODERATION IN KULONPROGO - Bambang Jatmiko (ASIAN PUBLISHER, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the regional economy, but in Kulon Progo Regency they still face obstacles, namely low financial literacy and management of organizational diversity. Data from the Cooperatives and SMEs Office shows that around 62% of MSMEs do not have standard financial records and only 48% are able to develop product innovations sustainably. This phenomenon has an impact on low competitiveness and business growth. This study aims to test and empirically prove the effect of the integration of financial literacy and organizational diversity on the development of MSMEs through innovation capabilities as an intervening variable and external environmental support as a moderating variable. The research method uses a quantitative approach with a survey method. The population in this study is all MSMEs including (culinary, crafts, trade, and services) with a total of 1300 MSMEs. While the sample in the study uses the Slovin formula, the number of samples is 306 MSMEs. The results of the study indicate that financial literacy and organizational diversity have a positive and significant effect on innovation capabilities. Innovation capability has been shown to mediate this influence on MSME development. Furthermore, external environmental support strengthens the relationship between innovation capability and MSME development. The theoretical implications of this study enrich the literature related to the integration of internal and external factors in MSME development. Practically, the research results provide recommendations for local governments to improve financial literacy training and create a business ecosystem that supports MSME innovation.